2020
DOI: 10.1039/d0cy00619j
|View full text |Cite
|
Sign up to set email alerts
|

Methanol oxidative dehydrogenation and dehydration on carbon nanotubes: active sites and basic reaction kinetics

Abstract: In situ active site titration, carbonyl group containing model catalysts, and kinetic analysis have been applied to reveal the nature of oxidized carbon nanotubes catalyzed methanol dehydration and oxidative dehydrogenation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Yan et al reported the oxidative dehydrogenation and dehydration of methanol over oxidized carbon nanotube catalyst (oCNT). 44 The catalytic efficiency of oCNT is comparable to that of industrial metal catalysts.…”
Section: General Types Of Supportsmentioning
confidence: 95%
“…Yan et al reported the oxidative dehydrogenation and dehydration of methanol over oxidized carbon nanotube catalyst (oCNT). 44 The catalytic efficiency of oCNT is comparable to that of industrial metal catalysts.…”
Section: General Types Of Supportsmentioning
confidence: 95%
“…In this context, high specific surface areas, tunable pore structure and surface chemistry, chemical inertness in a wide range of conditions as well as high thermal and electrical conductivities render carbon the material-of-choice for a variety of catalytic applications. Transformations involving carbon materials reach from energy conversion processes (e. g. fuel cell, [1] electrochemical water splitting [2] ) over hydrogenation (e. g. catalyst supports for Fischer-Tropsch-Synthesis [3] ) and dehydrogenation reactions (e. g. catalysts for the dehydrogenation of ethyl benzene [4,5] and alcohols [6][7][8] ), all the way to acid-base catalysis. Concerning acid catalysis, extensive work has been carried out focusing on metal-free, solid acid catalysts obtained by functionalization of carbon materials with heteroatoms such as O, S or P. [9] From a technical point of view, especially O functionalized carbons represent appealing solid acids, since established oxidation processes allow functionalization to be carried out on an industrial scale, achieving high densities of surface groups.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Strikingly, dimethyl ether (DME) was indeed observed as the main product of the conversion of methanol (MeOH) over MWCNTs in presence of oxygen at 320 °C. [7] Since especially DME is a promising candidate for the application as a sustainable, synthetic diesel fuel and represents an important intermediate in a hypothetical methanolbased circular economy for the production of various hydrocarbons, exploring high-temperature-acidic carbon materials as catalysts for DME production is of high interest. However, in order to enable a targeted catalyst design, identification of the responsible acidic centers as well as comprehension of the underlying mechanism of their formation are a prerequisite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Even carbon nanotubes were found to exhibit catalytic activity in the methanol conversion to DME. 16 For the direct route, bifunctional catalysts containing Cu, Zn, and Al are typically used. [17][18][19] Metal oxides modified with heteropolyacids 20 and mixed metal oxide-zeolite 21,22 catalysts for CO 2 hydrogenation to DME have been also reported recently.…”
Section: Introductionmentioning
confidence: 99%